Influence of Potential Hydrogen (pH) on the Growth of Bacillus cereus IMB-11 during Hydrocarbon Degradation in vitro - Sayuti, Irda; Zulfarina, Zulfarina; Widodo, Teguh Juliantani (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
This study aims to determine the pH variation of the growth of Bacillus cereus strain IMB-11 in degrading diesel fuel. The research was conducted in the Laboratory of PMIPA, FKIP, Universitas Riau while total petroleum hydrocarbon (TPH) was measured in the solid residue in the Laboratory of the Faculty of Civil and Environmental Engineering, ITB. This research was conducted in November 2019 – March 2020. The study was designed in a completely randomized design with 3 treatments and 3 replication groups. The media used are SMSS media with the addition of pH 6.5; pH 7.0; and pH 7.5, which was added with diesel fuel as much as 5% and bacterial isolates of Bacillus cereus strain IMB-11. The test parameter was the optical density (OD) of bacterial growth of Bacillus cereus Strain IMB-11 which was monitored using a spectrophotometer for 6 days and the measurement on the level of degradation or TPH diesel fuel using the Gravimetric method. Based on the research, the moderate pH of 7.0 was the best condition for strain growth with an OD of 5.8 with 26.95% of degradation rate of diesel fuel in vitro.